A solvent-free, transparent, self-healing polysiloxanes elastomer based on unsaturated carboxyl-amino ionic hydrogen bonds. (16th July 2021) - Mo, Jiaheng; Chen, Xinyu; Fu, Yubing; Li, Rui; Lin, Yaling; Zhang, Anqiang
Abstract: Ionic hydrogen bonding elastomers (IHSEs) as functional materials with a favorable self-healing ability and sensitive response to pH or heat have been increasingly investigated, yet most of these IHSEs are based on carbon chains with amino and carboxyl functional groups. Herein we describe an ionic hydrogen-bonded supramolecular polydimethylsiloxanes (PDMS) elastomer containing amino and unsaturated carboxyl groups produced via a facile and completely solvent-free synthesis route. Unsaturated carboxyl-grafted PDMS (UCS) and saturated carboxyl-grafted PDMS (SCS) were synthesized by reacting amino-grafted PDMS (APS) with maleic anhydride and succinic anhydride by simple mixing, respectively. The fact that IHSEs could be obtained by mixing UCS and APS while the mixture of SCS and APS was viscous fluid reveals difference of strength of ionic hydrogen bonds formed by unsaturated/saturated carboxyl groups with amino groups. To the best of our knowledge, it is the first time to investigate the role of unsaturated carboxyl groups which are conjugated with CC on the strength of the ionic interactions. Stronger ionic hydrogen bonds from unsaturated carboxyl-amino complex were further confirmed by NMR titration. The mechanical properties and self-healing ability may be fine-tuned by adjusting the ion cross-linking density and –COOH and –NH2 feed ratios. Furthermore, excess unsaturated carboxyl groups make IHSEs practically adhesive. We hope to further investigate the cross-linking mechanism of the ionic interactions inside the supramolecular network and to create a facile method to create supramolecular elastic systems. Graphical abstract: Image 1 Highlights: Unsaturated carboxyl were firstly used to construct supramolecular elastomers (IHSEs). Facile and completely solvent-free route to obtain IHSEs. Reversibility of ionic hydrogen bonds endows IHSEs with self-healing ability.